Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.3 - Polynomial and Rational Functions - Exercise Set - Page 596: 48



Work Step by Step

If $Q(x) = 4x^2-6x+3$ and $R(x) = 5x^2-7$ $Q(x) - R(x) = 4x^2-6x+3 - (5x^2-7) = 4x^2-6x+3-5x^2+7 = -x^2-6x+10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.